Super Cats - Rees, Gwyneth (London Bloomsbury, 2019)
Cats with superpowers! This brand-new series from bestselling author Gwyneth Rees is every young animal lover's dream come true. Perfect for fans of Holly Webb, Alex T. Smith, and those who want their animal stories with a bit more action! When Tagg discovers that his parents have superpowers, his life is changed forever. And just to think, all this time he thought he was an ordinary cat. Suddenly a whole new world opens up before his eyes. His mum has the most extraordinary claws. His dad is super strong. What will Tagg's power be? He can't wait to find out! But when a new cat arrives in town, things aren't quite what they seem. Nemesissy is a sleek lilac Siamese with the power to hypnotise humans. Under her orders, more and more kittens are disappearing. Unfortunately for Nemesissy she messes with the wrong cats when she targets Tagg and his new friend, Sugarfoot - they may be kittens, but they are SUPER!
3-5
Keywords: Language